Arduino UNO based Autonomous Train System - A., Kavithamani; S., Aakash; V., Krithick Roshan; S., Shobana; V., Vigneshwari; S, Nithish Ram K (Journal of ISMAC, 2025)
This study presents the design and implementation of an “Autonomous Train System” intended to improve safety, efficiency, and reliability in modern railway operations. The proposed system integrates advanced technologies, including GPS modules, infrared and ultrasonic sensors, RF communication, and microcontroller-based control units to facilitate real-time obstacle detection, automatic braking, and inter-train communication. By continuously monitoring track conditions and nearby trains, the system can dynamically determine risk and execute timely responses, significantly reducing the chance of human error. The inclusion of GPS-based distance measurement using the Haversine formula ensures accurate positioning and collision avoidance. Additionally, the use of wireless communication allows trains to exchange location and status data, enhancing coordination and safety. The system’s compact design, cost-efficiency, and scalability support its adoption in both urban and intercity networks. This autonomous approach not only improves operational dependability but also sets the foundation for intelligent transportation systems in the future of railway infrastructure.
Keywords: Driverless Train; Communication Protocols; Obstacle Detection; Train Control; Satellite Communication; GPS; Sensors; Transceiver Communication